Inflammatory and haematological markers in the maternal, umbilical cord and infant circulation in histological chorioamnionitis. - Rebecca A Howman; Adrian K Charles; Angela Jacques; Dorota A Doherty; Karen Simmer; Tobias Strunk; Peter C Richmond; Catherine H Cole; David P Burgner (PLoS ONE, 2012)
The relationship between histological chorioamnionitis and haematological and biochemical markers in mothers and infants at delivery, and in infants postnatally, is incompletely characterised. These markers are widely used in the diagnosis of maternal and neonatal infection. Our objective was to investigate the effects of histological chorioamnionitis (HCA) on haematological and biochemical inflammatory markers in mothers and infants at delivery, and in infants post-delivery.Two hundred and forty seven mothers, delivering 325 infants, were recruited at the only tertiary perinatal centre in Western Australia. Placentae were assessed for evidence of HCA using a semi-quantitative scoring system. Maternal high sensitivity C-reactive protein (hsCRP), procalcitonin, and umbilical cord hsCRP, procalcitonin, white cell count and absolute neutrophil count were measured at delivery. In infants where sepsis was clinically suspected, postnatal CRP, white cell count and absolute neutrophil count were measured up to 48 hours of age. The effect of HCA on maternal, cord and neonatal markers was evaluated by multivariable regression analysis.The median gestational age was 34 weeks and HCA was present in 26 of 247 (10.5%) placentae. Mothers whose pregnancies were complicated by HCA had higher hsCRP (median 26 (range 2-107) versus 5.6 (0-108) mg/L; P<0.001). Histological chorioamnionitis was associated with higher umbilical cord hsCRP (75(th) percentile 2.91 mg/L (range 0-63.9) versus 75(th) percentile 0 mg/L (0-45.6); P<0.001) and procalcitonin (median 0.293 (range 0.05-27.37) versus median 0.064 (range 0.01-5.24) ug/L; P<0.001), with a sustained increase in neonatal absolute neutrophil count (median 4.5 (0.1-26.4)×10(9)/L versus 3.0 (0.1-17.8)×10(9)/L), and CRP up to 48 hours post-partum (median 10 versus 6.5 mg/L) (P<0.05 for each).Histological chorioamnionitis is associated with modest systemic inflammation in maternal and cord blood. These systemic changes may increase postnatally, potentially undermining their utility in the diagnosis of early-onset neonatal infection.